Observation of Cyclosporin A: Sustained Release Intraocular Lens Implantation in Rabbit Eyes. (2nd November 2022) - Teng, He; Sun, Jing; Wen, Kai; Han, Guoge; Tian, Fang
Abstract: Purpose: To observe the performance of cyclosporine A (CsA)-loaded intraocular lens (IOLs) implanted into rabbit eyes. Methods: To prepare a PLGA-based CsA-sustained release IOLs and study the in vitro drug release. Forty-two New Zealand white rabbits were randomly and equally divided into three groups, and all right eyes underwent phacoemulsification. In group A, a common polymethylmethacrylate (PMMA) IOLs was implanted, while polylactide-glycoli acid (PLGA-loaded)-PMMA-IOLs was implanted in group B, and CsA-PLGA-PMMA-IOLs was implanted in group C. All experimental eyes were examined by slit-lamp microscopy. In addition, fundoscopy and the number of corneal endothelial cells, anterior chamber flare grading, and the number of aqueous humor cells were assessed at different time points post-surgery. The wet lens capsule was weighed and histological examination was performed 6 months post-operation. Results: In the early post-operative period, the inflammatory reaction of anterior chamber in groups A and B were more severe than group C. The initial appearance of PCO in group C was much later than the other two groups ( F = 68.91; p = 0.000), and PCO grade in group C was much lower than the other two groups (χ 2 = 36.07; p = 0.000). The mean weights of wet lens capsules in groups A and B were significantly heavier than group C ( F = 134.88; p = 0.00). Histological observation showed no obvious toxic reaction in the intraocular tissues of the CsA-PLGA-PMMA-IOLs group, and the proliferation and accumulation of lens epithelial cells in groups A and B were greater than in group C. Conclusion: CsA-sustained release IOLs can effectively prevent PCO in rabbit eyes without defined intraocular toxicity.